The work stress, occupational burnout, coping strategies and organizational support of elite sports coaches in Sichuan Province: the mediating role of organizational support - Yu, Liang; Cheng, Liang (Frontiers in Psychology, 2024)
This study involving humans were approved by the study was conducted according to the guidelines of the Declaration of Helsinki, and approved by the Ethics Committee of the Sichuan Sports College (2023.12). All the participants have signed an informed consent form in all participants.LY and LC: designing this study, writing initial draft and revision, revising language and content, supervision, project administration, and funding acquisition. LC: making figure and table. LY and LC: rechecking the manuscript and putting forward suggestions for amendment. All authors contributed to the article and approved the submitted version.